Prestasi dan budaya kerja kakitangan awam di Kabupaten Nunukan, Kalimantan Utara, Indonesia - Nuraida, Muhammad Aris (2024)
The success of an organisation relies heavily on its human resources, which function as the primary driving force behind its operations. The achievement of organisational goals is typically shaped by various factors, both direct and indirect, that are closely linked to the operational framework, with work culture particularly significant. This study seeks to identify the factors influencing the job performance of public sector employees in Kabupaten Nunukan, Indonesia with a specific focus on the empowerment of work culture. A quantitative approach was employed through the use of questionnaires, with a sample of 300 respondents from the Aparatur Sipil Negara (ASN). Data analysis was conducted using mean analysis, correlation analysis and linear regression analysis. The findings from the mean analysis indicated that both job performance and the empowerment of work culture were at a moderate level. Additionally, the correlation analysis revealed significant relationships between job performance and factors such as commitment, work discipline and work motivation. To gain a more in-depth understanding of the factors influencing work culture, the regression analysis identified 12 variables affecting commitment, 15 variables influencing work discipline, and 11 variables impacting work motivation. This study aims to provide a clearer perpective on the actual challenges faced by ASN in enhancing job performance. ASN plays a crucial role within the administrative system, serving as intermediaries between upper and lower levels of governance. As such, effective and strategic policies can be developed to ensure that the service delivery system of the Kabupaten Nunukan government operates at its optimal level, aligning with the vision of the Republic of Indonesia: "terwujudnya Indonesia maju yang berdaulat, mandiri dan berkeperibadian berdasarkan gotong royong" —the realisation of an advanced, sovereign, self-reliant Indonesia, founded on the principle of mutual cooperation.